Skolas un slēpti disfunkcionālo ģimeņu sadarbības iespējas socializācijas procesa sekmēšanai. - Stuģe, Jana (Latvijas Universitāte, 2009)
Maģistra darbā ”Skolas un slēpti disfunkcionālo ģimeņu sadarbības iespējas socializācijas procesa sekmēšanai ”apskatītas socializācijas problēmas slēpti disfunkcionālajās ģimenēs un to iespējamie risinājumi, skolai sadarbojoties ar ģimenēm. Teorētiskajā daļā lasāms par slēpti disfunkcionālo ģimeņu fenomenu sabiedrībā, problēmām, kas, nenovērtējot šo problēmu, varētu rasties ilgtermiņā; tāpat stāstīts par šādu ģimeņu tipiem, pētījumiem, kā arī par to ietekmi uz bērna socializācijas procesu. Pētījuma daļa veikta Rīgas 19.vidusskolā, un tajā apzināti un apkopoti pedagogu sniegtie dati par bērniem, kas aug slēpti disfunkcionālajās ģimenēs, izveidota šo bērnu uzskaite, apkopoti dati par nopietnākajām socializācijas problēmām. Tika aptaujāti arī apzinātie bērni un apkopoti dati par viņu sniegtajām atbildēm. Tālākajā darbā gaitā ieskicēts sadarbības plāns situācijas uzlabošanai, un darbu noslēdz secinājumi.

The Master’s thesis “Cooperation opportunities between schools and subtly dysfunctional families to facilitate socialisation process” deals with socialisation issues in subtly dysfunctional families and looks at potential solutions that might be arrived at as a result of family and school cooperation. The theory chapters describe the phenomenon of subtly dysfunctional families in the society and outline the problems that, if left unidentified, may develop in the longer term. The theory part also details the types of such families, lists the studies carried out and dwells on the effect of such a family on the child’s socialisation processes. The research on which the empirical part of the thesis has been based was carried out in Riga High School No. 19. The empirical part provides a summary and quantification of the data submitted by the teachers with regard to the children growing up in subtly dysfunctional families. It also includes an analysis and discussion of the data on such children not failing to list the gravest socialisation problems. The identified children were requested to fill in a questionnaire and the resulting data are respectively summarised in Chapter 5. The thesis also develops recommendations as to the potential cooperation schemes to improve the situation and, in its final part, lists the conclusions.
Possibilities of sghool and latently dysfunctional families for promoting the socialization process.
Keywords: Pedagoģija